ROLE OF PREFRONTAL CORTICAL CALCIUM-INDEPENDENT PHOSPHOLIPASE A(2) IN ANTINOCICEPTIVE EFFECT OF THE NOREPINEPHRINE REUPTAKE INHIBITOR ANTIDEPRESSSANT MAPROTILINE - Chew, Wee-Siong (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
10.1016/j.neuroscience.2016.10.037